Gimnasia laboral como propuesta en el tratamiento del sedentarismo en los docentes de la Universidad Técnica de Babahoyo - Rodriguez Garcia, Nayeli Lisbeth (2022)
The present study was developed with the objective of analyzing labor gymnastics as a proposal in the treatment of sedentary lifestyle in teachers of the Technical University of Babahoyo, since it was possible to demonstrate the presence of a problem, a problem associated with sedentary lifestyle, for which reason developed a non-experimental, descriptive investigation from its quantitative bases, with the intention of giving objectivity to the data obtained, applying as an instrument the international questionnaire of physical activity IPAQ to 13 teachers of the technical university of Babahoyo, 11 full-time and 2 a part-time, obtaining as results low levels of mets (metabolic index units) which classified the data in a level one assessment, which means that they do not practice the amount of physical activity adequate to overcome sedentary lifestyle, thus it was evidenced its presence in their lifestyle, therefore, it was decided to elaborate a plan that contributes to the treatment of sedentary lifestyle in teachers of the Technical University of Babahoyo through labor gymnastics.